2009
DOI: 10.1155/2009/542562
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Control of an Arm Exoskeleton Joint with Active-Compliant Actuation System

Abstract: This paper presents the methodology followed on the design of a multi-contact point haptic interface that uses a bio-inspired control approach and a novel actuation system. The combination of these components aims at creating a system that increases the operability of the target, and, at the same time, enables an intuitive and safe tele-operation of any complex robotic system of any given morphology. The novelty lies on the combination of a thoughtful kinematic structure driven by an active-compliant actuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…There are also hybrid solutions in the literature [ 89 , 146 , 147 , 148 ] that use various types of sensors even under conditions of hydraulic actions [ 149 ], and sometimes authors speak explicitly about the sensor fusion approach [ 126 , 150 ]. An interesting solution, even if it presents a low level of accuracy and precision, consists of measuring the electricity absorbed by a motor of an exoskeleton in terms of the current and voltage [ 151 ] in order to know the mechanical power delivered by the motor in terms of the torque and speed due to the knowledge of the electromechanical characteristics of the motor itself.…”
Section: Analytical Reviewmentioning
confidence: 99%
“…There are also hybrid solutions in the literature [ 89 , 146 , 147 , 148 ] that use various types of sensors even under conditions of hydraulic actions [ 149 ], and sometimes authors speak explicitly about the sensor fusion approach [ 126 , 150 ]. An interesting solution, even if it presents a low level of accuracy and precision, consists of measuring the electricity absorbed by a motor of an exoskeleton in terms of the current and voltage [ 151 ] in order to know the mechanical power delivered by the motor in terms of the torque and speed due to the knowledge of the electromechanical characteristics of the motor itself.…”
Section: Analytical Reviewmentioning
confidence: 99%
“…It is shown that the remote control of arm movements helps to achieve a light weight and low inertia design properties. Besides, the cable-driven architecture can eliminate possible joint misalignment between the human upper limb and exoskeleton, thus reducing the chances of injuries for the patient during robotic rehabilitation [16,17]. However, bio-inspired control methods are proposed in those studies, although they are not derived from the control principles of natural biological systems, and they do not take into account that the bio-inspired control mostly depends on the nonlinear properties of natural muscles.…”
Section: Introductionmentioning
confidence: 99%
“…The research described in the previous paragraph suggests that the legs of bioinspired legged robots should be operated like a passive and linear spring by using stiffness or force control. For example, on the arms [ 5 ], hands [ 6 ], legs [ 7 ], or exoskeleton [ 8 ]. Though ideally the spring-like behavior can be achieved by controlling multi-degree-of-freedom (DOF) legs to act like a spring, empirically this approach is extremely challenging because artificial actuators such as electric motors have limited power density in comparison to biological actuators such as muscles.…”
Section: Introductionmentioning
confidence: 99%